PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 1 SIAK HULU - Julfa Wista; Rini Dian Anggraini; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aims of research is to improve learning process and to increase student mathematics achievement with applying the learning model of Problem Based Learning. This research is classroom action research. The subject of this research is student of class VIIJ SMP Negeri 1 Siak Hulu in academic years 2018/2019. Subject which amounted to 32 students, consist of 16 boys and 16 girls. The research consist of two cycles, each cycle have four stages, which are planning, implementation, observation, and reflection. The research instrument consists of learning materials and instruments for collecting data. Learning materials used in this research are the syllabus, Lesson Plan and Activity Sheets. The instruments of data collection and students mathematic tests. The observation sheets is analyzed in qualitative desciptive, while the students mathematic tests is analyzed in quantitative descriptive. The qualitative descriptive show an improvement of learning process prior to the action on the first and second cycle. Most of students are very confidence and active in learning process, such as while they are finishing mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. The results of this study indicate the number of students who reached Minimum Mastery Criteria of knowledge increase from basic score to first test and second test. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (28,13%) to the first test (59,37%) to the second test (71,89%). For the skills of the first test (65,62%) to the second test (87,50%). From these data it can be concluded that the application of Problem Based Learning can increase mathematics achievement from the students at class VIIJ SMP Negeri 1 Siak Hulu in academic years 2018/2019 for the subject Aritmatika Soaial.Key Words: Students’ Mathematic Achievement, Problem Based Learning,Class Action Research